Imlementation of The Curriculum of State Vocational School 9 Padang By Preparing Graduates Who Are Ready To Work - Saqinah, Natasya; Andriani, Cici; Elida, Elida; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study, titled Implementation of the Curriculum at SMK Negeri 9 Padang in Preparing Work-Ready Graduates, focuses on the culinary arts program. It aims to analyze the planning, implementation, evaluation, and challenges of curriculum application. The research employed a descriptive qualitative approach using in-depth interviews, observations, and documentation. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings show that the involvement of industries in curriculum planning remains limited; however, practice-based learning such as teaching factory and industrial internships effectively improve students’ culinary skills. Graduate employment absorption increased from 44.9% to 74%. The main constraints include limited practice facilities and insufficient practice time. This study highlights the importance of continuous collaboration between schools and industries to produce competent and work-ready vocational graduates.